Virtual reality on perioperative anxiety in pediatric patients: A narrative review - Sabrina Soledad Domene; Daniela Fulginiti; Gabriela D Briceno Silva; Paloma Frei; Gladys Amalia Perez Santiago; Marisa Gasbarra; Isabella Peters; Alexis O’Connell; Ernesto Calderon Martinez (Digital Health)
Preoperative anxiety is a common response to stress specifically in the pediatric population exhibiting heightened susceptibility to it. High anxiety levels can negatively impact the quality of anesthesia, increase analgesia requirements, and result in significant postoperative pain. The present review synthesizes recent literature regarding virtual reality (VR)’s efficacy in mitigating preoperative anxiety in the pediatric population. Virtual reality is a nonpharmacological intervention that alleviates pain and preoperative anxiety through cognitive distraction, redirecting patients’ focus away from discomfort. Neurophysiologically, VR engages the prefrontal cortex, influences pain pathways, and reduces pain-related activity in the thalamus, insula, anterior cingulate cortex, and primary and secondary somatosensory cortices. Evidence indicates that VR is more effective in reducing anxiety compared to other nonpharmacological strategies, particularly benefiting younger children, who tend to exhibit higher levels of engagement in magical thinking compared to adolescents. Virtual reality presents numerous clinical applications, including facilitating postsurgical recovery, assisting in physiotherapy for neuromuscular disorders, and providing nonpharmaceutical analgesia. However, its integration into healthcare faces several challenges, such as the high costs of acquiring and maintaining the equipment, particularly in resource-limited settings. Moreover, the limited number of studies examining VR exposure with small nonrepresentative sample sizes further constrains its recommendation as an anxiety-reduction technique. Despite its limitations, substantial evidence suggests that VR has the potential to alleviate preoperative anxiety and mitigate the psychological responses of pediatric patients. Standardized research protocols featuring larger sample sizes and expanded access to VR across various levels of care are necessary.